Percutaneous Endoscopic Jejunostomy Tube Placement for Treatment of Severe Hyperemesis Gravidarum in Pregnancy - David Kruchko DO; Natasha Shah MD; Charles Broy MD; Dean Silas MD (SAGE Publishing, 2020)
Hyperemesis gravidarum is a common disease. Most patients are effectively treated with conservative measures, but gastric feeding and, rarely, post-pyloric feeding can be necessary. A 27-year-old woman, G3P2002, with a history of refractory hyperemesis in previous pregnancies, required placement of a nasojejunal tube but was removed due to an oropharyngeal ulcer. Endoscopic placement of a percutaneous endoscopic transgastric-jejunostomy (PEG-J) tube caused resolution of her symptoms. Twelve days after placement, the distal tube became dislodged and was endoscopically replaced with hemoclip anchoring in the jejunum. PEG-J tube placement is a safe and effective option for nutritional support in refractory hyperemesis gravidarum.